Folding of a natural variant of human apolipoprotein A-I associated with atherosclerosis. Micro environment and function - Díaz Ludovico, Ivo (2019)
Human apolipoprotein A-I, the major protein fraction of the High density lipoproteins(HDL) has long been considered a protective factor against the development of coronaryheart disease. However, either the deletion of a residue (Lys 107) or a chronic proinflammatory scenario resulted in the deposition of the protein within atherosclerosisplaques and associated to amyloid deposits. The presence of protein aggregates in thislandscape may suggest that a shift from the native conformation should result in a lossof function. To elucidate whether structural changes may be responsible for the proteindeposition and misfunction, we compared by biophysical approaches the deletion mutantLys107-0 structure with respect to the protein with the native sequence (Wt), eitherfreshly resuspended or after controlled oxidation. A red shift in intrinsic Trp fluorescenceand a higher binding of Bis ANS indicate a more flexible structure of this mutant, whichpreserves lipid binding capacity. Structural flexibility seems to be clue to this role, as alower efficiency in intra-chain cross linking resulted in lower blockage of dimirystoylphosphatidyl choline (DMPC) clearance.In order to analyze the effect of oxidation on protein structure and function, Wt andLys107-0 were oxidized and protein structure reevaluated. Trp and Met oxidation isdetected by Mass Spec, and an increased tendency of the proteins to aggregate isobserved by microscopy approaches, which is especially evident for the deletion mutant.Nevertheless, lipid clearance and solubilization is not significantly modified, indicatingthat the integrity of the salt bridge network involving polar residues in the centraldomain of the protein is not essential to this function. More research will be done todetermine the importance of single residues in protein function.